2018
DOI: 10.1016/j.compbiomed.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale smeared finite element model for mass transport in biological tissue: From blood vessels to cells and cellular organelles

Abstract: One of the basic and vital processes in living organisms is mass exchange, which occurs on several levels: it goes from blood vessels to cells and organelles within cells. On that path, molecules, as oxygen, metabolic products, drugs, etc. Traverse different macro and micro environments - blood, extracellular/intracellular space, and interior of organelles; and also biological barriers such as walls of blood vessels and membranes of cells and organelles. Many aspects of this mass transport remain unknown, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…On the other hand, various biobarriers may limit the extravasation of nanodrugs into solid tumor, and in certain cases, such as in the case of liposomal nanocarriers, the gain in the therapeutic index is primarily related to reduction of toxicity rather than to efficacy increase . Indeed, nanodrugs, including liposomes, must overcome various and sequential biobarriers to reach their targets, such as the endothelial barrier, the membrane of tumor cells, and subcellular organelles (e.g., nucleus and lysosomes); they must resist to enzymatic degradation in the blood, should avoid sequestration by phagocytes of the reticuloendothelial system (RES) and molecular efflux pumps, and must migrate against adverse oncotic and interstitial pressures in the tumor . Some of these barriers are related (or consequent) to the abnormal structure of the tumor vasculature, which is typically characterized by highly disorganized architecture, by vessels with dilated and excessive branching, shunts, and fenestrations, and by vessels lacking basement membrane or with fewer pericytes, compared to normal vessels .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, various biobarriers may limit the extravasation of nanodrugs into solid tumor, and in certain cases, such as in the case of liposomal nanocarriers, the gain in the therapeutic index is primarily related to reduction of toxicity rather than to efficacy increase . Indeed, nanodrugs, including liposomes, must overcome various and sequential biobarriers to reach their targets, such as the endothelial barrier, the membrane of tumor cells, and subcellular organelles (e.g., nucleus and lysosomes); they must resist to enzymatic degradation in the blood, should avoid sequestration by phagocytes of the reticuloendothelial system (RES) and molecular efflux pumps, and must migrate against adverse oncotic and interstitial pressures in the tumor . Some of these barriers are related (or consequent) to the abnormal structure of the tumor vasculature, which is typically characterized by highly disorganized architecture, by vessels with dilated and excessive branching, shunts, and fenestrations, and by vessels lacking basement membrane or with fewer pericytes, compared to normal vessels .…”
Section: Introductionmentioning
confidence: 99%
“…The surface areas entering into matrices of the connectivity elements are as given in Equation (21). The above concept has been implemented for diffusion and fluid transport through complex systems consisting of capillary network and tissue, with inclusion of the hydrophobicity effects in the connectivity elements (Kojic et al, 2014(Kojic et al, , 2017a(Kojic et al, , 2018, and with improvements of accuracy of the smeared methodology achieved by the correction function introduced in Milosevic et al (2018a). The robustness and applicability of the smeared model are demonstrated (Milosevic et al, 2018b), where the CSFE is extended for modeling drug release from a complex mesh of drug-loaded nanofibers.…”
Section: Smeared Model For Field Problemsmentioning
confidence: 99%
“…The above concept has been implemented to diffusion (including convection) and fluid transport through capillary network and tissue, with demonstration of accuracy of the smeared methodology (Kojic et al 2017a(Kojic et al , 2017b(Kojic et al , 2018. To improve the smeared model accuracy, a correction function was introduced in (Milosevic et al 2018a).…”
Section: ( ) ( )mentioning
confidence: 99%
“…We have selected a small 50x50 micron size 2D tissue sample taken from images of cancerous tissue (E. J. Koay, MD Anderson Cancer Center, Houston, Kojic et al 2018) shown in Fig. 3a.…”
Section: A Numerical Examplea Tissue Sample From a Pancreatic Tumormentioning
confidence: 99%
See 1 more Smart Citation